Four new HLA class I alleles in Spaniards, HLA‐A*32:01:23, HLA‐B*18:01:24, HLA‐B*18:72:02 and HLA‐C*12:166. (4th July 2016) - Balas, A.; Pacho, A.; Arrieta, A.; García‐Sánchez, F.; Vicario, J. L.
Abstract : Characterization of four new human leukocyte antigen (HLA) class I alleles, A*32:01:23, B*18:01:24, B*18:72:02 and C*12:166 .